Fit to Teach?—Cardiorespiratory Capacity, Vitamin D3, and Ferritin in Physical Education Teachers With Specialization in Dance. Issue 4 (April 2021) - Schmidt, Mike; Ohlendorf, Daniela; Groneberg, David A.; Wanke, Eileen M.
Abstract : Abstract: Schmidt, M, Ohlendorf, D, Groneberg, DA, and Wanke, EM. Fit to teach?—Cardiorespiratory capacity, vitamin D3, and ferritin in physical education teachers with specialization in dance. J Strength Cond Res 35(4): 1156–1164, 2021—Numerous studies have shown that good cardiorespiratory capacity is of great importance for a healthy and long-term professional career as a dancer. Although the cardiorespiratory demands during teaching can reach into the submaximal intensity range, current data on the objective physical fitness of this occupational group are still missing. The aim of this pilot project was to determine selected cardiorespiratory parameters. In addition, measurements of the vitamin D3 (25(OH)D3) and iron balance as well as a subjective assessment of dance teachers' (DTs) fitness were performed. Twenty-one DTs (f: n = 18, m: n = 3) aged 48.2 ± 9.3 years were examined for cardiorespiratory performance within the framework of maximum bicycle spiroergometry. In addition, the self-perception of DTs' fitness was examined as well as the serum vit D3 levels and ferritin concentration in the blood. The cardiorespiratory fitness of DTs can be assessed as average (maximal oxygen consumption, V[Combining Dot Above]O2 max = 29.5 ± 7.1 ml·k −1 ·min −1 ; physical working capacity, PWCmax = 165.0 ± 44.4). The DTs seemed to underestimate or overestimate their own capacity. Laboratory diagnostics showed that the 25(OH)D3 levels (21.8 ± 8.5 ng·ml −1 ) and serum ferritin values (102.4 ± 35.0 g·dl −1 ) were not optimal for almost the entire sample. In view of the physical occupational requirements, an increase in aerobic cardiorespiratory fitness by endurance-oriented basic training for DTs seems advisable. In addition, the substitution of vit D3 is worth being discussed.